THE EFFECT OF AUTHENTIC LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE ENGAGEMENT WITH INTERNAL COMMUNICATION AS MEDIATOR VARIABLE IN MILLENNIAL GENERATION OF POLRI (INDONESIAN NATIONAL POLICE) - Pardede, Charles Djohan; Soeling, Pantius Drahen (Advances in Social Sciences Research Journal, 2020)
Employee engagement improvement or engagement of Polri (Indonesian National Police) employees especially millennial generation or Y generation is very important and one of challenges for National Police organization. Millennial generation has different characteristic with the previous generation where millennial generation tends to have a flexible culture (difficult to control), adaptive leadership style, as well as very familiar with the use of technology so that they are more creative and innovative. This research aims to analyze the effect of authentic leadership, organizational culture on employee engagement of millennial generation in National Police planning function by the use of mediation variable, that is, internal communication. The research method which was used to test the hypothesis was Explanatory Survey Method, while the explanation of the relationship between variables was tested and analyzed by Structural Equation Modeling (SEM). A number of 450 respondents who are Polri members in the plannning function with a background of millennial generation as the sample in this research. The result of the research explained that variables of authentic leadership and organizational culture gave positive effect on employee engagement either directly or by internal communication mediation. Furthermore, authentic leadership variable also had positive effect on organizational culture and internal communication. Based on this research result, it was determined that authentic leadership, organizational culture and internal communication could improve and support the employee engagement especially millennial employees in National Police planning function either directly or by internal communication mediation.